Use of protective behavioral strategies and blackout experience among mandated college students. (September 2022) - Carey, Kate B.; Tempchin, Jacob; DiBello, Angelo M.; Mastroleo, Nadine R.
Highlights: Protective behavioral strategies predict past-month alcohol-related blackout. Manner of drinking and limiting/stopping drinking were significant predictors. Use of serious harm reduction strategies was unrelated to alcohol-related blackout. Avoidance of blackouts is facilitated by only some protective behavioral strategies. Abstract: Objective: Alcohol-induced blackouts are experienced by approximately half of college students who drink. People who use protective behavioral strategies (PBS) tend to experience fewer alcohol-related consequences of drinking, but the relationship between PBS and blackouts is unknown. This study examines the associations among the use of protective behavioral strategies and blacking out. Methods: Participants were 484 college students, aged 18–22 (56% male, 51% first-year), who were mandated to complete alcohol education following an alcohol violation. Before the intervention, participants completed questionnaires that included questions about past month peak consumption, alcohol-related consequences, marijuana use frequency, and frequency of PBS use. Logistic regression analyses were conducted to evaluate how use of PBS was related to the odds of experiencing a blackout, controlling for consumption and other risk factors. Results: Participants endorsing greater overall use of PBS had decreased odds of having experienced a blackout. However, this association depended on the type of PBS being used. Participants endorsing greater use of PBS regarding manner of drinking and stopping/limiting drinking had decreased odds of having experienced a blackout, but those who endorsed greater use of PBS relating to serious harm reduction did not. Conclusions: This study adds nuance to the idea that PBS protect against adverse alcohol-related consequences. Only PBS that serve to limit or slow consumption appear to be protective against experiencing blackouts. Research on specific associations between types of PBS and consequences may lead to improved outcomes in interventions that incorporate PBS.